140 Adoptive transfer of T cells surface-tethered with IL-12 promote antigen spreading for enhanced anti-tumor efficacy. (9th November 2020) - Jaehger, Ditte; Stokes, Kate; Halldórsdóttir, Hólmfridur; Pratama, Alvin; Ahmad, Gulzar; Nardozzi, Jonathan; Sackton, Katharine; Jones, Douglas; Andresen, Thomas
Abstract : Background: Acquired resistance is a major limiting factor for durable T cell therapies in solid tumors. Antigen escape pathways such as insufficient antigen coverage or loss of target antigen remain major resistance mechanisms that need to be addressed in order to expand the field of T cell therapies.Interleukin-12 (IL-12) is a potent stimulator of innate and adaptive immune cells that holds strong potential for cancer immunotherapy, but its clinical utility has been limited by high systemic toxicities. We have previously shown that tethering an IL-12 immunocytokine to the surface of T cells prior to adoptive cell transfer (ACT) safely improves anti-tumor efficacy by promoting T cell function specifically in the tumor. Here, we demonstrate that cell-tethered IL-12 delivers adjuvant activity that leads to priming and expansion of by-stander, tumor-specific T cells, and thereby counteract common immune escape pathways. Methods: Adjuvant activity of IL12-tethered pmel T cells, reactive towards the gp100 antigen of B16 tumors, was evaluated in the B16-OVA syngeneic mouse model. Notably, adoptive transfer of IL12-tethered pmel T cells, but not pmel T cells alone, resulted in proliferation of endogenous tumor infiltrating lymphocytes. To assess whether this reflected tumor-specific T cell responses, we used dextramer staining against non-targeted, tumor-specific antigens and found that both abundance and activation increased following cell-tethered IL-12 treatment. Encouraged by these findings, the OT-1 model was used to track epitope spreading to tumor-specific naïve T cells. Following treatment with IL-12-tethered PMEL T cells, we tracked the proliferation and tumor engraftment of labelled, naïve OT-I T cells, which are reactive towards the non-targeted OVA antigen. Results: Cell-tethered-IL12, but neither ACT nor ACT and systemically administered IL-12, induced proliferation and engraftment OT-1 T cells in tumor-draining lymph nodes (tdLNs) and tumors of B16-OVA-bearing mice. This effect was antigen-dependent as the OT-I T cells were not primed in B16.F10 (OVA antigen-negative) tumors. Mechanistically, this priming was associated with IL-12-induced increases in activation and tdLN infiltration of cross-presenting dendritic cells (cDC1) as well as increased presentation of the SIINFEKL epitope of OVA specifically on this subset of dendritic cells. Conclusions: Together, our findings suggest that tethering IL-12 to tumor-specific T cells prior to adoptive transfer promotes epitope spreading through the combination of tumor cell-killing induced by the ACT therapy and IL-12-induced activation of cDC1s in the tdLN. This adjuvant activity from T cell-tethered IL-12 holds promise for overcoming antigen escape pathways that limit the efficacy of antigen-specific T cells against heterogeneous tumors